PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SMP SE-NIAS BARAT - Gulo, Soziduhu; Nadeak, Bernadetha; Tampubolon, Hotner (Jurnal Dinamika Pendidikan, 2021)
The principal has an important role in improving the performance of his teachers. The results of preliminary observations found that principals are authoritarian by making decisions without involving teachers. Gives a bad impression to subordinates who later builds a culture that affects the teacher's performance. This type of research is quantitative using a survey method with a correlation approach, related to the purpose for"examining the influence of the principal's leadership style and organizational culture on teacher performance in junior high schools in Nias"West. Teachers of State Junior High Schools in West Nias which constitute the study population by taking a sample of certified teachers spread across 38 schools. The influence of the principal's leadership style on teacher performance based on the results of the study was 17.5%, the influence of organizational culture on teacher performance was 16% and the influence of the principal's leadership style and organizational culture on teacher performance was 20.6%. for other reasons.